THE SOCIAL SECURITY OF DUANO COMMUNITY PANGLIMA RAJA VILLAGE INDRAGIRI HILIR REGENCY RIAU PROVINCE - Rilanda, Suci; Nugroho, Firman; Amrifo, Viktor (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Poverty is always there in human life, thus requiring a comprehensive preventionefforts, integral and sustainable. Crisis and economic uncertainty make socialsecurity mechanism to maintain economic survivalitas fishing communities is veryimportant. Indragiri Hilir Regency Community of Duano that there is a social reality,Community of Duano Society is included in an isolated environment. People ofIndragiri Hilir more familiar Community of Duano as â€œthe seaâ€ which calls used bythe Malays to the people or communities who lives in the boat or live in costal sea,strait, and estuaries, livelihood as fisherman fishing, shrimp and shells. This studyaimed to identify the forms of social security whatever there is in the community ofDuano. Analyze the social security mechanisms that exist in the community ofDuano. The method used in this research is qualitative research methods in theimplementation of this study used a qualitative descriptive approach. Data obtaineddirectly from informants who work as fishermen in Community of Duano throughinterviews. The results showed the from of social security in the Community ofDuano (1) social security education (2) social security health (3) social security foodand clothing (4) social security work and enterprise (5) social security housing (6)social security old-age (7) social security as an orphan and family benefits. Sosicalsecurity mechanisms that exist in communities of Duano (1) formal social security(2) informal social security.Keywords: Analysis, Social Security, Community Tribal Duano